Dynamics of energy transfer in the LH2 antenna complex of the purple bacterium Rhodobacter sphaeroides - Polívka, Tomáš; Herek, Jennifer L.; Pullerits, Tõnu; Dahlbom, Mats; Hunter, C. Neil; Sundström, Villy (Springer Series in Chemical Physics, 1998)
Transient absorption spectra and kinetics are used for detailed studies of energy transfer dynamics within the B850 ring of the LH2 antenna of the purple bacterium Rb. sphaeroides. The initial exciton relaxation was found to occur within the first 100 fs and no temperature dependence of this process was observed. Trnsient abcorption spectra of the LH2 antenna complex at 6 K revealed a new spectral band around 880 nm as a result of energy distribution of the lowest exciton states of B850 rings at cryogenic temperatures.